The Hospital as An Ideological State Apparatus and Disciplinary Agent as Seen through the Main Character in Kenzaburo Oe’s A Personal Matter - Ardhana, Alwi Atma; Wardani, Elisa Dwi (Universitas Sanata Dharma, 2015)
This study attempts to examine the disciplining process of the main character in Kenzaburo Oe’s novel entitled A Personal Matter under the light of structural-Marxism theories on ideology, interpellation and hegemony. Bird, the main character, is described as an unruly character that often reacts differently from other characters in dealing with his life. However, at the end of the novel Bird becomes a different person after a series of disciplining process in the hospital. The hospital has employed disciplinary methods such as panopticism, examination and normalizing judgment on Bird. Those disciplinary actions are largely based on the ideology of Marugakae as the ideology of Japanese society. In turn, the disciplinary actions are to inject the ideology of the state to Bird. The shift in Bird’s characteristics has rendered him one of the common people subordinated by the common system or ideology. In this sense, the prevailing system in Japanese society as seen in the novel continues to exist.Keywords: power, ideology, interpellation, hegemony, panopticism, Marugakae